THYMIC STROMAL LYMPHOPOIETIN EXPRESSION IN NASAL EPITHELIAL CELLS OF ALLERGIC ASTHMATICS - Moorehead, Amy (My University, 2020)
Thymic stromal lymphopoietin (TSLP), an epithelial-derived cytokine, has a critical role in the development of allergic inflammatory responses and have been implicated in type 2 allergic disease, including asthma, allergic rhinitis, and atopic dermatitis. Genetic polymorphisms in the TSLP gene are among the most commonly cited variants associated with asthma and allergic disease, however, the functional effects of these polymorphism are not fully understood. The objective of this study was to investigate the role of a TSLP polymorphism in the Th2 inflammatory responses of the nasal epithelium, as well as in responding to nasal allergen provocation and intranasal corticosteroid treatment. We cultured nasal epithelial cells from allergic asthmatic subjects and examined cytokine and chemokine secretions and gene expression profiles in response to polyinosinic:polycytidylic acid treatment. To explore the functional consequences of the rs1837253 polymorphism we analyzed the two TSLP gene isoforms, as they have shown dichotomous effects, however, no associations were found between rs1837253 genotype and the expression of TSLP and gene isoforms. We did not find any associations of TSLP or cytokine production between genotypes, or in relation to response to nasal allergen challenge or corticosteroid treatment. Exploration of local and systemic effects of the rs1837253 SNP did not show any differences in response to INCS treatment in vitro or ex vivo. We did demonstrate that nasal epithelial cell-derived factors are capable of stimulating eosinophil/basophil colony forming units in the absence and presence of exogenous IL-3. Overall, the results indicate a role of the nasal epithelium in driving eosinophil/basophil differentiation and highlight the complexity of gene-environment interactions and the mechanisms of asthma and allergic inflammation.
Keywords: asthma; allergy; thymis stromal lymphopoietin; rs1837253; nasal epithelial cells